2013
DOI: 10.1186/1746-1596-8-186
|View full text |Cite
|
Sign up to set email alerts
|

Association of a polymorphism in PON-1 gene with steroid-induced osteonecrosis of femoral head in Chinese Han population

Abstract: BackgroundTreatment with steroids covers a wide spectrum of diseases in clinic. However, some users are suffering from serious side effects of steroid administration, while we enjoy the benefit it brings about. Osteonecrosis of the femoral head (ONFH) is a troublesome one among them. Recent studies have demonstrated that lipid metabolism disorder may play a vital role in pathogenesis of ONFH and mutation of the paraoxonase-1 (PON-1) gene may be involved in the occurrence of this disease. However, the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In 2007, Hadjigeorgiou et al [ 25 ] researched the role of PON1 polymorphisms in ONFH with/without WML in Greek population and the common polymorphisms M55L, R192Q were selects, the results indicated that PON1 192QQ genotype carriers had a significant increased risk to suffer from ONFH and WML, but not M55L polymorphism. In Chinese Han population, Wang et al [ 26 ] conducted a case-control study about PON1 rs662 (R192Q) polymorphism and ONFH risk and also gained a similar conclusion that rs662 was associated with the susceptibility to steroid-induced ONFH. However, the steroid users without developing ONFH were employed as control.…”
Section: Discussionmentioning
confidence: 94%
“…In 2007, Hadjigeorgiou et al [ 25 ] researched the role of PON1 polymorphisms in ONFH with/without WML in Greek population and the common polymorphisms M55L, R192Q were selects, the results indicated that PON1 192QQ genotype carriers had a significant increased risk to suffer from ONFH and WML, but not M55L polymorphism. In Chinese Han population, Wang et al [ 26 ] conducted a case-control study about PON1 rs662 (R192Q) polymorphism and ONFH risk and also gained a similar conclusion that rs662 was associated with the susceptibility to steroid-induced ONFH. However, the steroid users without developing ONFH were employed as control.…”
Section: Discussionmentioning
confidence: 94%
“…Environmental factors include type of prosthesis, implant design, material, surgical technique, fixation method, and postoperative rehabilitation procedure have been widely studied [ 13 , 14 ], but more and more attention is paid to the genetic factors like single nucleotide polymorphisms (SNPs). SNPs are genetic variations that are considered biologically normal and can be found in at least 1% of the population, which may contribute towards individual susceptibilities to certain pathological conditions [ 15 , 16 ]. Various gene SNPs of GNAS1, TNF-238, TNF-a, IL6-174, MMP1, MMP2, and et al were reported to be associated with increased prosthetic loosening.…”
Section: Introductionmentioning
confidence: 99%
“…ONFH is a disorder caused by the interactions with complex genetic and environmental factors 9 . A series of genes polymorphisms have been showed to associate with ONFH risk 10 , 11 , 12 while the effects of genes polymorphisms in RANKL/RANK/OPG signaling pathway on the development of ONFH have been remained unclear. RANK/RANKL/OPG pathway plays an important role in the pathogenesis of RA and osteoporosis due to the crucial molecular pathway for coupling between osteoblasts and osteoclasts.…”
Section: Discussionmentioning
confidence: 99%